Benefits of Cooperation between Buyers and Providers: a study in the field of information and communications technology - Brito, Eliane Pereira Zamith; Mariotto, Gabriel (Review of Business Management, 2013)
This study examined the relationships between manufacturers and their distributors and retailers in the Information Technology sector. The characteristics of these relationships were identified, particularly cooperation between buyers and suppliers, and its impact on the relationship performance. Four cooperative behaviors represented the idea of cooperation. Efficiency and effectiveness were used as a performance evaluation of the relationship. Interviews with company managers were the main source of data. This research identified a significant level of cooperation within relationships, and exchange of information, joint problem-solving and flexibility were the most visible behaviors. The positive effect of cooperation in partner satisfaction concerning the relationship was observed, leading managers to the decision to buy and to a positive experience as to the relationship. The study also showed that effectiveness feeds back the process.